Strategic Guidance and Counseling Management in Dealing With Puberty at MTs Negeri 17 Jombang - Nur Annisa; Nur ‘Azah; Abdullah Aminuddin Aziz (International Journal of Education Management and Religion, 2025)
Guidance and counseling management plays a vital role in adolescent development by helping students navigate the complex physical, emotional, and social transitions of puberty. This study aims to describe the management of guidance and counseling in dealing with puberty at MTs Negeri 17 Jombang. It employs a qualitative descriptive approach using a case study design, enabling an in-depth understanding of real-world implementation within a madrasah setting. Data were collected through in-depth interviews, observations, and documentation involving counseling teachers, school leaders, and other key stakeholders. The findings show that guidance and counseling management is carried out systematically through planning based on student needs and aligned with the school calendar, implementation of services such as individual counseling, group counseling, and home visits, and reflective evaluation involving feedback from teachers, students, and parents. Supportive factors include institutional commitment, counselor competence, parental involvement, and a religious environment, while constraints include limited time and low student openness. This study offers practical insights into the implementation of structured counseling strategies to assist students in navigating the physical and emotional changes of puberty within a madrasah context.